The ‘curse of Horaeomorphus’ (almost) lifted. Revision of misplaced species from Madagascar, Comoros and Mascarenes (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2024)
Fifty species of Stenichnini that occur in Madagascar, Comoros and Mascarenes are currently placed in Horaeomorphus L.W. Schaufuss. Twenty-eight of them have been originally described as Horaeomorphus, twenty as Euconnus Thomson subgenus Anthicimorphus Franz (subgeneric name later synonymized with Horaeomorphus), one as Cyrtoscydmus Motschulsky (species later transferred to Euconnus (Anthicimorphus)), and one as Scydmaenus Latreille subgenus Vinsoniana Lhoste (subgeneric name later synonymized with Horaeomorphus). Horaeomorphus manjakotompoi Franz syn. n. is placed as a junior synonym of H. ankaratranus Franz; H. anjouanensis Franz syn. n. and H. robinsoni Franz syn. n. are placed as junior synonyms of H. adamsoniae Franz; H. andranomandery (O’Keefe) syn. n. is placed as a junior synonym of H. ambatolampyensis (Franz). Vinsoniana Lhoste syn. n. has been erroneously synonymized with Horaeomorphus by Franz, and here is placed as a junior synonym of Tetramelus Motschulsky. Alloconophron (Franz) syn. n. is placed as a junior synonym of Anhoraeomorphus Franz. The taxonomic status of the following species is changed: Anhoraeomorphus ankaratranus (Franz) comb. n., Anhoraeomorphus andapensis (Franz) comb. n., Anhoraeomorphus ivelonanus (Franz) comb. n., Anhoraeomorphus procerus (Franz) comb. n., Anhoraeomorphus sakarahanus (Franz) comb. n., Anhoraeomorphus adamsoniae (Franz) comb. n., Anhoraeomorphus ambodivoangyi (Franz) comb. n., Anhoraeomorphus ankaratrae (Franz) comb. n., Anhoraeomorphus anosyensis (Franz) comb. n., Anhoraeomorphus barbatus (Franz) comb. n., Anhoraeomorphus bialatipenis (Franz) comb. n., Anhoraeomorphus compactus (Franz) comb. n., Anhoraeomorphus diegoi (Franz) comb. n., Anhoraeomorphus gigas (Franz) comb. n., Anhoraeomorphus globosus (Franz) comb. n., Anhoraeomorphus inermis (Franz) comb. n., Anhoraeomorphus lambomakandroi (Franz) comb. n., Anhoraeomorphus longicollis (Franz) comb. n., Anhoraeomorphus manangotryanus (Franz) comb. n., Anhoraeomorphus maximus (Franz) comb. n., Anhoraeomorphus moheliensis (Franz) comb. n., Anhoraeomorphus nudipennis (Franz) comb. n., Anhoraeomorphus roussettensis (Franz) comb. n., Anhoraeomorphus sikorai (Franz) comb. n., Anhoraeomorphus vadoni (Franz) comb. n., Anhoraeomorphus vellyi (Franz) comb. n., Euconnus (s. str.) tananarivensis Franz stat rev., Euconnus (Tetramelus) aequalis Franz stat. rev., Euconnus (Tetramelus) andasyi Franz stat. rev., Euconnus (Tetramelus) andasyensis Franz stat. rev., Euconnus (Tetramelus) angustissimus Franz stat. rev., Euconnus (Tetramelus) anthicimadagascanus Jałoszyński stat. rev., Euconnus (Tetramelus) comorensis Franz stat. rev., Euconnus (Tetramelus) gomyi Franz stat. rev., Euconnus (Tetramelus) imaitsanus Franz stat. rev., Euconnus (Tetramelus) lacertosus Franz stat. rev., Euconnus (Tetramelus) matsaboryi Franz stat. rev., Euconnus (Tetramelus) mauritiensis (Lhoste) comb. n., Euconnus (Tetramelus) paravulgaris Franz stat. rev., Euconnus (Tetramelus) pellifer Franz stat. rev., Euconnus (Tetramelus) sogaensis Franz stat. rev., Euconnus (Tetramelus) tamatavae Franz stat. rev., Euconnus (Tetramelus) tenuissimides Newton stat. rev., Euconnus (Tetramelus) vulgaris (C. Schaufuss) stat. rev., Clepsydraphes nitidulus (Franz) comb. n. (type species of Clepsydraphes gen. n.), and Contreuconnus ambatolampyensis (Franz) comb. n. (type species of Contreuconnus gen. n.). As a result of these actions, the distribution of Horaeomorphus is demonstrated to be restricted to the Australo-Oriental region, including the Himalayan and Far Eastern Oriental/Palaearctic border zones, and Melanesia. Most of the above-mentioned species are redescribed, but the type specimens of nine of them were not available for detailed study and their revised placement is based on descriptions and illustrations by previous authors. These include A. ankaratrae, A. bialatipenis, A. gigas, A. longicollis, A. vadoni, E. aequalis, E. mauritiensis, E. paravulgaris, and E. tananarivensis. Therefore, the ‘Horaeomorphus curse’ causing so much taxonomic chaos, will end once the status of the species tentatively placed in Anhoraeomorphus and Euconnus is verified.